Limbic system abnormalities in episodic cluster headache: a 7T MRI multimodal study - Xinyu Wang; Luhua Zhang; Yongqin Xiong; Mengmeng Hou; Shuhua Zhang; Caohui Duan; Song Wang; Xiaoyu Wang; Haoxuan Lu; Jiayu Huang; Yan Li; Zhixuan Li; et al. (The Journal of Headache and Pain)
Abstract Background Although the limbic system has long been thought to be involved in the pathophysiology of cluster headache, inconsistencies in imaging studies of episodic cluster headache (eCH) patients and limited understanding of the specific regions within the limbic system have prevented a full explanation of its involvement in the disease. Therefore, we performed multimodal imaging analysis using 7 T MRI with the aim of exploring structural–functional abnormalities in subregions of the limbic system and their relationship with clinical features. Methods In this cross-sectional study, we employed 7T MRI to investigate structural (volumetric) and functional (fractional amplitude of low-frequency fluctuations (fALFF), regional homogeneity (ReHo)) alterations in limbic subregions (hypothalamus, thalamus, amygdala, hippocampus) among 69 in-bout but outside the attacks eCH patients and 63 healthy controls (HCs). Automated volumetry and resting-state functional MRI analyses were performed after adjusting for age, Generalized Anxiety Disorder scale, sex (and intracranial volume when evaluating volumetric measures). Then functional-structural coupling indices were computed to assess network-level relationships. Results In eCH patients, volumes in right anterior inferior and right posterior of hypothalamus, left molecular_layer_hippocampal-head, left lateral-nucleus and left Central-nucleus on the headache side, as well as left tuberal inferior and left tuberal superior of hypothalamus, and right parasubiculum on the contralateral side were significantly altered compared with HCs (P < 0.05). Additionally, the volume of the right anterior inferior was positively correlated with the duration of last headache episode. After false discovery rate correction, widespread alterations in fALFF and ReHo values were observed among hypothalamic, thalamic, hippocampal, and amygdalar subregions, some of which correlated with clinical measures. Furthermore, the structure–function coupling indices in the right anterior inferior and the left lateral geniculate nucleus on the headache side differed significantly between eCH patients and HCs. Conclusions Our findings demonstrate that in-bout but outside the attacks eCH patients present anatomical and functional maladaptation of the limbic system. Moreover, the observed dissociation between localized abnormalities and largely preserved network coupling—except in the hypothalamus and thalamus—suggests that these two regions may be particularly susceptible to eCH-related dysfunction, while broader brain networks retain compensatory capacity in pathological states. These findings refine potential neuromodulation targets and highlight the value of ultrahigh-field imaging in eCH research.